A Double-blind, Randomized Controlled Trial of Ciplukan (Physalis angulata Linn) Extract on Skin Fibrosis, Inflammatory, Immunology, and Fibrosis Biomarkers in Scleroderma Patients - Sumartini Dewi; Harry Isbagio; Erni Hernawati Purwaningsih; Nyoman Kertia; Rianto Setiabudy; Siti Setiati (Acta Medica Indonesiana, 2020)
Background: scleroderma is an autoimmune disease characterized by organ fibrosis, resistant to standard treatment. It is suspected the addition of Physalis angulata Linn. (Ciplukan) extract as adjuvant therapy can improve the scleroderma skin fibrosis. The aim at this study is to evaluate the effect of ciplukan extract as adjuvant on scleroderma skin fibrosis in standard therapy, based on modified Rodnan skin scale (MRSS), inflammatory biomarkers, immunology and serum fibrosis. Methods: double-blind, randomized clinical trial was performed in scleroderma patients with stable disease at Cipto Mangunkusumo hospital and Hasan Sadikin hospital during November 2015−March 2017 who met the selection criteria and continued to receive standard therapy. The subjects were randomly allocated into two groups: the study group received the ciplukan  extract 3 x 250 mg / day for 12 weeks and the placebo group. Examination of MRSS, ESR, P1NP, BAFF and sCD40L was performed every 4 weeks until the end of the study. Results: fifty-nine subjects completed the study. They consisted of 29 subjects of the treatment group and 30 of the placebo group, with an average age of 41 (SD 9) years, the proportion of women: male = 9 : 1. There was a significant improvement of skin fibrosis in the study group with a highly significant decrease in MRSS (35.9% VS 6.3%, p <0.001) and a relative decrease in P1NP levels (17.8% VS 0.7%, p = 0.002). No decrease in ESR, BAFF and sCD40L levels in both groups. There was a weak but significant positive correlation between MRSS with P1NP levels (r = 0.236, p = 0.036). Conclusion: Ciplukan extract with dose 3 x 250 mg for 12 weeks as adjuvant on scleroderma standard therapy alleviates skin fibrosis significantly based on MRSS and P1NP levels.